Empowering Orphaned Children Through English Language Learning: A Community Engagement at Yayasan Yatim Daarul Ma’wa - Abdul Basit Basit; Ahmed Mehmood Qureshi (Journal of Community Engagement, 2025)
This report involves the evaluation of a community-service project which was done on 14 May 2025 involving 42 orphaned children at the Yayasan Yatim Daarul Ma’wa in Depok, Indonesia. The final aim was to boost the communicative confidence group of the learners and achieve a sense of cultural pride by engaging them in an exposure to the English language. The intervention part comprised a one workshop intervention supported by preliminary needs assessment, interactive pedagogical process, and reflective feedback process. Tasks to be undertaken included (1) situational ice-breakers, (2) mini-lessons on usefulness of the English language in the world, (3) conversation session, and (4) open question and answer session on barriers to learning. The practices of practical self-study (media immersion and extensive reading) were explicitly modelled and provided in a take-home toolkit. Short-term outcomes indicated that 87 percent of the respondents (n 42) had statistically significant changes in the wishes to speak English (before and after self-rating, p 0.05) and asserted to possess more cultural esteem. The proof among the involved students of the university (n = 12) was the growth of civic awareness and the heightened consumer desire to participate in outreach in the subsequent future. The findings support the idea that short, pedagogically focused service-learning can build orphan linguistic self-efficacy and social responsibility in university students both at the same period of time, and, that is why, it could be one of the examples of educational community engagement. Keywords: community intervention, English language Learning, Orphaned Children.